Statistical software adoption behaviour among Indonesia's undergraduate students - Zaitul; Rizki Mulyani, Sitti; Ridwan, Muhammad; Ilona, Desi (Journal of physics. Conference series, 2019)
Technology usage among students is a must since revolution industry 4.0. However, there is a limited study about technology adoption among student. This study's objective is to explore the influence of external factors on usefulness and ease of use the statiscal software. Besides, this paper also analyses the association between ease of use and usefulness on behavioural intention to use SPSS among accounting students. By extending technology acceptance perspective (TAM), this study develops eight hypotheses. Seventy-three accounting students were registered at subject of business research method in accounting department, Bung Hatta University, participated in this study. Structural equation model-path least square is used to analyse the primary data. The result shows that computer attitudes has a positive relationship with usefulness. In addition, SPSS self-efficacy also has a positive relationship with ease of use. Further, statistic learning value is positively related to usefulness. Finally, ease of use is positively related to behavioural intention to use SPSS. Out of eight hypotheses being developed, four hypotheses is supported and the rest is rejected. Theoretical and practical implication is discussed in this article.